2019
DOI: 10.1002/chem.201806133
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Non‐linear Chemical and Physical (CAP) Dynamics of Signal Amplification By Reversible Exchange (SABRE)

Abstract: What is the most significant result of this study?Signal amplification by reversible exchange (SABRE) with parahydrogen is au nique method to boost the NMR signal by several orders of magnitude. Many effects that govern SABRE were described before, or at least mentioned in the literature. Ac omprehensive model bringing together the separate pieces, however, was missing so far.T his is what we did here.Invited for the cover of this issue are Andrey N. Pravdivtsev and Jan-Bernd Hçvener from Kiel University.T he … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 103 publications
(119 reference statements)
0
31
0
Order By: Relevance
“…Depending on the simulated experiment, different source operators can be used. Simulations were performed using the MOIN spin library; the source code is available online …”
Section: Resultsmentioning
confidence: 99%
“…Depending on the simulated experiment, different source operators can be used. Simulations were performed using the MOIN spin library; the source code is available online …”
Section: Resultsmentioning
confidence: 99%
“…Hence the results portrayed here detail a route to probe for reaction intermediates in catalysis based on how they affect the evolution of polarisation under SABRE as a function of temperature. While a range of theoretical studies have been reported that detail how the propagation of spin polarisation during SABRE occurs, it is clear that if theoretical predictions 20,30,31,38,39 are to accurately map onto experimental data, 40 they will need to take into account contributions from a range of species in solution. We expect that these results will be of interest to those seeking to model SABRE and those involved more generally in the study of catalysis.…”
Section: Experimental Sabre Resultsmentioning
confidence: 99%
“…4,9,10 Consequently, the efficiency of SABRE is highly dependent on the lifetime of the complex which must match the propagating resonance condition leading to transfer. [11][12][13] It also relies on setting the magnetic field the sample experiences during the transfer step to a value of around 60 G when 1 H nuclei are targeted, but much lower mG fields are needed for 15 N and 13 C nuclei. [14][15][16] Given these constraints, the level of NMR signal enhancement can be improved through catalyst design and by sharing the hyperpolarisation source p-H 2 with fewer receptor spins in conjunction with deuterium labelling which also reduces relaxation effects.…”
mentioning
confidence: 99%
“…The role of level‐anti‐crossings in the transfer of polarization has also been explored, and has been shown to be the most efficient at low magnetic fields . Recently, a more simplified approach has been investigated, that takes in to account non‐linear and chemical and physical dynamics to produce a master equation to provide insight in to the SABRE mechanism …”
Section: Resultsmentioning
confidence: 99%